A Data Warehouse Application Framework for Negotiation in Procurement - Karmakar, R; Sarkar, BB; Chaki, N (International Journal of Computer Sciences and Engineering, 2025)
Negotiation is a long standing process during procurement. Traditional negotiation needs a complete knowledge about the business process and its legacy systems. Depending upon the size, volume and the nature of the business the criticality of the negotiation process varies. For an efficient negotiation of a large and medium size enterprise historical information’s plays a vital role. A Data Warehouse along with the OLAP measures provide that support. Further the introduction of Internet the entire negotiation process is changed. The traditional transaction process is replaced by the automated transactions. The real market place is now become a virtual market place and opens new avenues for enterprises to do smart business through electronic agents. The agents are multifaceted, intelligent and autonomous and can be made enriched with the enhancement of business logics. In this paper we propose a generic framework on e-procurement process with the help of a case study in steel industry.